Out-of-hospital cardiac arrest in Cork, Ireland. Issue 6 (15th June 2012) - Henry, Kieran; Murphy, Adrian; Willis, David; Cusack, Stephen; Bury, Gerard; O'Sullivan, Iomhar; Deasy, Conor
Abstract : Background: Out-of-hospital cardiac arrest (OHCA) in Ireland accounts for approximately 5000 deaths annually. Little published evidence exists on survival from OHCA in this country to date. We aimed to characterise and describe 'presumed cardiac' OHCA in Cork City and County attended by the Ambulance Service. Methods: Dispatch records, ambulance patient records and hospital records for a 1-year period were examined for patient demographics, OHCA characteristics, interventions and patient outcomes. Results: There were 231 'presumed cardiac' OHCAs attended over the study period; 130 (56%) were in urban locations and 101 (44%) in rural. OHCAs were lay-witnessed in 20% (n=46), and 22% (n=50) received bystander CPR. Shockable rhythm was present in 36 cases (16%) on initial assessment, and there was no difference in presence of shockable rhythm between urban and rural OHCAs (18% vs 13%, p=0.31). Resuscitation was attempted in 176 cases (77.5%), of whom 27 (15%) achieved return of spontaneous circulation and 13 (7.4%) survived to leave hospital. Survival when the initial rhythm was shockable was 16.7% (6 of 36 patients). Despite longer response times for rural compared with urban OHCAs (median (IQR) 16.5 (11.0–23.5) vs 9 (7–12) min, p<0.001), survival to leave hospital alive where resuscitation was attempted was similar (7.4% vs 7.4%, p=0.99, respectively). Conclusion: A survival rate of 16.7% in shockable rhythms indicates scope for improvement which would influence the overall survival rate which was found to be 7.4%. Real-time feedback of performance and quality of the continuum of patient care through a clinical-quality cardiac arrest registry would monitor and incentivise such initiatives.